Digital tools devising pedagogical approaches: exploring the potential of rule-based design in developing student competencies. (18th December 2017) - Ibrahim, Mohamed S.; Chase, Scott C.
Abstract: It is believed that behind the conception of generative design systems there are many design theories, methods and models as well as reasoning systems that contribute to offer more than images, data or software. The research assumes that computational models have the potential to aid devising pedagogical approaches for developing students design competences. It adopts a rule-based tool, and uses grammar-based projects, charrettes and analytical tasks to explore and evaluate the development of design capacities in several architectural schools. Abstract : Students' interpretation of rubber pattern formation